Tahapan siklus estrus pada mencit betina (Mus Musculus) serta perubahan fisiologi tubuh - Nisa, Rany Hilyatan; Rahma, Suhaila (Maliki Interdisciplinary Journal, 2024)
The estrous cycle is a physiological change process that occurs periodically in most female mammals to regulate fertility. The estrous cycle occurs with the aim of female animals being ready to mate. The estrous cycle is divided into four phases: the Proestrous phase, the Estrous phase, the Metestrous phase, and the Diestrous phase. The method used in this study was direct observation of experimental animals by observing hormonal changes, behavior during the estrous phase, and histology through the preparation of vaginal smears. The results of this observation showed that the four experimental animals used were in four different estorus phases. This can be observed through the presence or absence of nucleated epithelial cells and cornified epithelial cells in the vaginal smear preparation.